Pseudomonas Putida Bacteraemia in a Haemodialysis Patient from Karnataka, India: A Rare Case Report - Karnaker, Vimal Kumar; Suchithra , Kokkarambath Vannadil; Ashraf, Asem Ali; Rehman, Rifah (Biomedical Sciences and Clinical Medicine, 2026)
Pseudomonas putida is a Gram-negative, non-fermenting bacillus traditionally considered a low-virulence environmental organism, but increasingly recognized as an emerging opportunistic pathogen in healthcare settings. Infections are most often reported in immunocompromised patients, particularly those with end-stage renal disease (ESRD), diabetes, malignancies, or indwelling medical devices. We report a case of P. putida bacteremia in a 69-year-old female with ESRD on maintenance haemodialysis, type 2 diabetes mellitus, and hypertension, who presented with acute breathlessness, vomiting, diarrhea, and altered sensorium. Blood cultures performed using the BacT/Alert® system grew P. putida, confirmed by VITEK 2 Compact and MALDI-ToF. The isolate was resistant to trimethoprim/sulfamethoxazole but remained susceptible to ceftazidime, cefepime, carbapenems, aminoglycosides, and fluoroquinolones. Empiric meropenem therapy was continued upon identification, leading to marked clinical improvement within five days. Four cycles of haemodialysis were administered; however, the patient was discharged against medical advice due to financial constraints, and follow-up cultures could not be obtained. This case underscores the clinical significance of P. putida as an emerging nosocomial pathogen in patients with multiple comorbidities. Rapid identification, timely initiation of effective empiric therapy, and antimicrobial stewardship are essential to improve patient outcomes and mitigate complications, particularly as multidrug-resistant strains of P. putida are increasingly reported worldwide.